Procedures manual from the Ethics Committee of Investigation in a hospital institution: an indispensable proposal - Tatiana Marañón Cardonne; Ivan Delgado Suárez; Llilian Vaillant Lora; Yaité Zaldívar Rosales (Centro Provincial de Información de Ciencias Médicas, 2017)
Ethics committees for investigation are those in charge of the review and evaluation processes of investigations in general and of the surveillance and control of ethical principles fulfillment. To such effects the procedures manual for the Ethics Committee of investigation from "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba, was designed on the base of updated national and international regulations, aimed at establishing a follow up methodology in the different processes that this Committee carries out.  For its elaboration 3 stages were accomplished such as: documental review, group discussion and experts consultations, in that order. It was structured taking into account first, a series of general contents and then, different procedures that lead its operation were established. Its implementation contributed decisively to the hospital recertification in good clinical practices.